THE INFLUENCE OF MORINGA OLEIFERA FINE POWDER FUNCTION ON HB LEVEL PREGNANT WOMEN TRIMESTER III WITH ANEMIA IN THE WORKING AREA OF MANGUNREJA HEALTH CENTER KAB. TASIKMALAYA - Santi Yuliastuti; Herni Kurnia (Poltekkes Kemenkes Tasikmalaya, 2022)
Anemia that occurs during pregnancy is one of the big problems that occur in developing countries, including Indonesia. Iron deficiency anemia in the mother can increase growth and development of the fetus during pregnancy as well as thereafter. An estimated 41.8% of pregnant women are saved from anemic world, lower than they should be due to iron deficiency. One of the government's policies to increase the nutritional needs of pregnant women is with the help of iron supplements. One of the herbs that can improve the nutrition of pregnant women and Hb levels is Moringa leaves. Moringa leaves contain vitamin A, vitamin B, vitamin C, calcium, iron, and protein in very high amounts that are easily digested by the human body. The purpose of this study was to study the comparison of Moringa oleifera leaf powder to hemoglobin levels in third trimester pregnant women with anemia. Research designs Quasi-experimental studies using unequal control group designs. This research was conducted in the Work Area of Mangunreja Public Health Center in Tasikmalaya City in 2019. The sample was taken by purposive sampling and the sample size was 36 respondents, 18 control groups and 18 regulatory groups. The results of the study, in the control group wolcoxon test results, the value of p = 0.602 0.05 while in the group treated the Wilcoxon test results, the value of p = 0.003 0.05, thus using flour Moringa oleifera powder. hemoglobin levels of third trimester pregnant women with anemia.Keywords: Anemia, Pregnant Women, Moringa leaf powder